2008
DOI: 10.2332/allergolint.o-06-461
|View full text |Cite
|
Sign up to set email alerts
|

Sputum Eosinophilia, Airway Hyperresponsiveness and Airway Narrowing in Young Adults with Former Asthma

Abstract: This study shows that subjects with long-term outgrown asthma continue to have airway eosinophilic inflammation, airway hyperresponsiveness and airway narrowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Teenagers who are asymptomatic could actually have pathological signs of sub-clinical asthma, persistent BHR, airway inflammation and thickening of the reticular layer of the airways basement membrane (73)(74)(75). On the basis of these large numbers of converging observations, current hypotheses focus on epithelial barrier function and it has been suggested that in asthma a structurally and functionally defective lower airways epithelium underlies abnormal responses to the inhaled environment leading to enhanced signalling between the airway epithelium and the Epithelial-Mesenchymal Trophic Unit (EMTU) and immune cells (76).…”
Section: Lifetime Course Of Asthmamentioning
confidence: 99%
“…Teenagers who are asymptomatic could actually have pathological signs of sub-clinical asthma, persistent BHR, airway inflammation and thickening of the reticular layer of the airways basement membrane (73)(74)(75). On the basis of these large numbers of converging observations, current hypotheses focus on epithelial barrier function and it has been suggested that in asthma a structurally and functionally defective lower airways epithelium underlies abnormal responses to the inhaled environment leading to enhanced signalling between the airway epithelium and the Epithelial-Mesenchymal Trophic Unit (EMTU) and immune cells (76).…”
Section: Lifetime Course Of Asthmamentioning
confidence: 99%
“…Even though there was not a strong association between the level of eosinophils during bronchiolitis and subsequent asthma, increased BHR may represent risk factors for future development of asthma, as indicated by other studies (1). Others have reported a continuing eosinophilic airway inflammation, BHR and airway narrowing in young adults with outgrown asthma (24). In the Tucson's study, BHR at the age of six was independently associated with asthma at the age of 22 (25).…”
Section: Eosinophils Bronchial Hyper-responsiveness and Lung Functionmentioning
confidence: 79%
“…Surprisingly, both groups of animals avoided anaerobic glucose metabolism during I/R, consistent with resistance from I/R injury. DBHB is protective during I/R [49][52], presumably from the ketone bodies direct entrance into the TCA cycle and the avoidance of the conversion of pyruvate to lactate and development of acidosis [53][55]. Similar metabolomes in both groups of AGS suggest that metabolic flexibility persists in AGS during the summer season.…”
Section: Discussionmentioning
confidence: 98%